Bedside identification of patients at risk for PVC‐induced cardiomyopathy: Is ECG useful?. Issue 7 (30th June 2017) - Garster, Noelle C.; Henrikson, Charles A.
Abstract: Background: Premature ventricular complexes (PVCs) are an underrecognized cause of cardiomyopathy. Standard 12‐lead electrocardiogram (ECG) has potential to direct attention toward at‐risk patients. Methods: We performed a single‐center, retrospective chart review of 1, 240 patients who completed ECG and Holter monitoring at Oregon Health and Science University Hospital between January 1, 2011 and December 31, 2013 to investigate the relationship of PVC frequency on ECG with burden on Holter. Primary outcome measures included PVC quantity on ECG, mean PVC quantity on Holter, and percentage of total beats on Holter recorded as PVCs. High PVC burden was defined as ≥10% of total beats. Results: Weighted mean percentages of total beats on Holter monitor recorded as PVCs were calculated for 0, 1, 2, and ≥3 PVCs on ECG and found to be 1.4% (n = 1, 128), 3.5% (n = 32), 4.3% (n = 25), and 16.6% (n = 55), respectively, which represent statistically significant differences (P < 0.001). The positive predictive value of at least three PVCs on ECG for ≥10% PVC Holter burden was 58%. Negative predictive value for 0 PVCs on ECG was 98%. The sensitivity and specificity of ECG to identify high PVC burden on Holter was 72% and 93.6%, respectively, when utilizing a positive ECG result as one PVC or more, and 44% and 98.9%, respectively, with ≥3 PVCs on ECG. The positive likelihood ratio corresponding to ≥3 PVCs on ECG was 40. Conclusion: These findings demonstrate that the number of PVCs on ECG can be utilized for quick bedside estimation of high PVC burden.